Analyses of Characteristics’ Sets of Low Speed Linear Electric Drives - Rinkevičienė, R.; Poška, A. J.; Darulienė, O. (Elektronika ir Elektrotechnika, 2004)
This article analyses calculation method of characteristics’ sets of low speed linear induction motors (LIM). Proposed more simple resistance formula of LIM sequential equivalent scheme accelerates static and dynamic characteristics’ sets calculation of LIM and linear electric drives. It was tested experimentally starting force of short-time duty cylindrical LIM dependence on a windings connection method. Tested parameters sets of LIM static and dynamic characteristics can be applied in designing of linear electric drivers. Ill.3, bibl. 11 (in Lithuanian; summaries in Lithuanian, English and Russian).